Palliative care in the elderly person by nurses in Urgency and Emergency Services: A scope review (Research, Society and Development, 2024)
It is common for people with advanced chronic diseases, especially the elderly, to seek urgent and emergency services at some point in their lives. These services are intended to address the situation that led the person to these locations, that is, measures to improve their health status at that moment. In many of these situations, the need for dialogue with the patient and their family members is perceived, explaining the situation regarding the evolution of the disease and its future course. This article aims to identify and map in the literature what perceptions and knowledge nurses have in palliative care for elderly people in emergency and emergency services. This is a scoping review following the recommendations of the Joanna Briggs Institute (JBI) and based on the guidelines of the Preferred Reporting Items for Systematic reviews and Meta-Analyses – extension for scoping reviews. The contents were analyzed in their similarities and differences, emerging four categories related to PC for elderly people in emergency and emergency services, namely: Interventions and management systems in care network services, tools; Nursing inserted in an interdisciplinary approach; Practical applications in the perception and understanding of PC in elderly people by nursing; and understanding of the demographic, clinical, and epidemiological profile in emergency and urgent care services. Practical interventions in care management, tools implemented with education and appreciation of user specificities, assistance focused on a network of emergency and urgent care services that value the quality of health care for the elderly, and the search for strategies to maintain, value, and improve care between management, multidisciplinary teams, and users in palliative care provide equitable dimensioning and valuing life over death.